United States military assistance an empirical perspective - Mott, William H. IV 1939- (Contributions in military studies, 2002)
This interdisciplinary study examines the relationships between the provision of military assistance and success in achieving donor aims in history and theory, based upon an initial proposition that the relationship between donor and recipient is a critical determinant of success or failure. Mott builds upon his previous research of general historical and Soviet case studies which focuses on four initial features of the wartime donor-recipient relationship: convergence of aims; donor control, commitment of donor military forces, and coherence of donor policies and strategies. To this foundation, he adds additional variables, recipient success, and regional efforts. The study presents a pattern for policy development and theoretical analysis in which military assistance is a viable, robust policy option and bilateral relationship with clear set of requirements, features, processes, and predictable results.